INSPIRING ENGLISH TEACHERS: INDONESIA TERTIARY EFL STUDENTS’ VOICE - Mobit, Mobit; Salim, Fatulloh; Krishnapatria, Kriswanda (Wiralodra English Journal, 2019)
This study aims to scrutinize tertiary students? voices against the teacher/ lecturer who inspires them. This study elaborates on two classes of English Language Study Program as the respondents. The data use a questionnaire containing several questions that elaborated the teachers? characteristics that can generate inspiration to the students. This study was designed by using the survey. Based on the data obtained it can be concluded that the teachers/ lecturers who inspire (tertiary) students are those who have the unambiguous characteristics of English teachers both characteristics and competencies. They are capable to develop concepts/ provide material that encouraged students easily comprehends the material, to color the process of learning in class with humorous atmosphere, and to make students laugh and refresh and to give suggestions as well.